Subversive Sixties in Ink: Underground Comix, Censorship, and Translation between the United States and Italy - Polli, Chiara (TTR)

(untitled) (Association canadienne de traductologie, 2022)
This study focuses on underground comix in the US and their reception in Italy, where different translations have been circulating since the late 1960s. Underground comix were the controversial product of the 1960s-1970s’ counterculture, that is, of a period of struggle and cultural renewal in US history. As taboo contents such as sex, drugs, and political dissent became the core of this needle-sharp graphic satire, underground cartoonists had to deal with media lynching, exclusion from distribution circuits, fines, and seizures of materials. The present contribution reconstructs the twisted relationships between underground comix and the different forms of censorship they faced in their homeland as well as in Italy, where they were translated by both militant and mainstream publishers in different time periods. This study focuses on Robert Crumb, the most famous underground cartoonist, and discusses a corpus of comics dealing with the theme of sexuality used to shock and subvert US morality. The compared analysis of multiple translations of the same stories, published between the 1970s and 2018, shows how the Italian reception of Crumb’s most provocative comics was impacted by a pre-selection of contents, practices of deliberate censorship of the original materials and, in particular, by the trivialisation of potentially subversive contents under the influence of the commedia sexy all’italiana film genre. It is maintained that, in the Italian context, Crumb’s sexually explicit works are not deemed controversial provided they are deprived of social criticism and re-interpreted within a comedic frame through translation. The latter argument paves the way for a reflection on how subversive materials can be “narcotized” (Eco, 2003, p. 139) by means of banalization, whose outcomes are similar to those that result from overt censorship.